Quantifying Zoonotic Risk from Cats (Felis catus, Felidae: Carnivora): A Systematic Meta-Analysis of Pathogen Prevalence - Handoko, Jully; Simanjuntak, Arya Marganda; Suyanto, Suyanto; Pengsakul, Theerakamol; Susana, Yuli; Maulana, Rian; Asni, Enikarmila; Indarjulianto, Soedarmanto (Universitas Airlangga, 2025)
Cats are known to be potential reservoirs for a variety of zoonotic pathogens. However, the overall prevalence of zoonotic pathogens in the cat population remains unclear amid growing concerns. This study aimed to measure the combined prevalence of zoonotic pathogens in cats through a systematic review and meta-analysis. Relevant literature reporting the prevalence of zoonotic pathogens in cats, published from 2015 to 2025, was collected from databases. A total of 49 studies met the inclusion criteria, encompassing a total sample size of 18,206 cats. A meta-analysis was performed using a random-effects model. Toxoplasma gondii, Bartonella henselae, and Campylobacter spp. were the most frequently reported pathogens, with pooled prevalence estimates presented with 95% confidence intervals (CIs). The I² statistic was used to assess heterogeneity. The combined prevalence of zoonotic pathogens in cats was estimated at 24% (95% CI: 17–32%). Considerable heterogeneity was observed among the studies (I² = 98.4%, p < 0.001), and this likely reflects differences in geographic region, diagnostic methods, and pathogen type. Individual study prevalences ranged from 0.02 to 0.97, with varying weights according to sample size and variance. This meta-analysis highlights the relatively high prevalence of zoonotic pathogens among cats. The relevance of applying a One Health perspective is emphasized by these findings for the development of evidence-based public health policies to reduce zoonotic risks at the community and global levels.